Pengaruh Latihan Small Side Games dengan Metode Pyramid terhadap Peningkatan Anaerobic Alaktasid pada Pemain Sepak Bola Usia Remaja (U-17) - Andika, Wildan; Imanudin, Iman; Rusdianto, Agus; Muhammad4, Fadli (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to evaluate the effects of Small-Sided Games (SSG) training with the Pyramid method on the improvement of alactic anaerobic capacity in U-17 Persib Academy football players. This study uses a quantitative approach with a pre-test and post-test design and applies the Running-Based Anaerobic Sprint Test (RAST) as a measurement tool. The research results indicate that the training intervention provided had a significant impact on the improvement of sprint speed, as reflected by the reduction in total sprint time and Fatigue Index in most participants. Statistical analysis through the normality test using the Shapiro-Wilk test shows that the pre-test data has a value (p-value = 0.999 > 0.05), while the post-test data has a value (p-value = 0.221 > 0.05). Because both p-values (Sig.) > 0.05, the data are normally distributed. And the statistical analysis through the paired sample t-test revealed a significant difference between the pre-test and post-test results (p-value = 0.029 < 0.05), confirming that SSG training is effective in improving anaerobic endurance and energy efficiency of the players. Conclusion, the small-sided games (SSG) method is recommended as a training strategy that can enhance the alactic anaerobic capacity in soccer players.Keywords: Anaerobic Alactacid, Fatigue Index, Football,  Small-Sided Games, Sprint.